THE INFLUENCE OF SCIENTIFIC APPROACH WITH CROSS LINE METHOD FOR MULTIPLICATION TOWARD STUDENT UNDERSTANDING ON THE CONCEPT OF MULTIPLICATION (International Conference on Elementary Education, 2018)
This study aims at determining the influence of scientific approach with cross line method for multiplication toward student understanding on the concept of multiplication. The type of study is a one-group experiment. The population of the study in the third-grade as much 80 students of the elementary school in Bandung. The sample of the study as much 38 children. The sampling technique was done by purposive sampling. The technique of collecting data using pre-test and post-test. The pre-test and post-test using 5 indicators understanding on the concept of multiplication. Data were analyzed using descriptive statistic. The results show that mean the pre-test 28 and mean the post-test 69. Also, 4 indicators understanding concept multiplication increased. Thus it can be concluded that the scientific approach with cross line method for multiplication proved to improving student understanding on the concept of multiplication.